Evaluation of Protective Effects of Aqueous Extract of S. Maydis on Liver Cytoarchitecture of Wistar Rats Induced with Carbonated Herbal Alcoholic Beverages (Orijin Bitters) - A. Agbortai; G. I. Eze; S. B. Olukayode; S. O. Innih (Journal of Applied Sciences and Environmental Management)
Alcoholic beverages are renowned as the most common types of alternative medicine, but the frequent over indulgence in the use of alcoholic beverages however, have been linked with a number of social and importantly health problems and death. Herbs, such as Stigma maydis, which have been used for centuries in treating various illnesses, play a major role in forming the basic platform of modern medicines. Consequently, this work evaluated the protective effects of aqueous extract of Stigma maydis (AESM) on the liver cytoarchitecture of carbonated herbal alcoholic beverage-induced Wistar rats using appropriate standard methods. A total of Thirty-six Wistar rats (180-190 g), were divided into groups (n=6). Group A: Control (untreated), Group B: Orijin bitters, Group C: Orijin bitters + AESM (200 mg/kg), Group D: Orijin bitters + AESM (600 mg/kg), Group E: AESM (200 mg/kg) and Group F: AESM (600 mg/kg). Oral administration lasted for 60 consecutive days. After sacrifice, the livers were harvested, fixed in 10% neutral buffered formalin, and processed for histological assessment using haematoxylin and eosin staining. The results showed administration of orijin bitters caused significant alterations to the cytoarchitecture of the liver, characterized by severe vascular ulceration, mild to severe vascular congestion, and infiltration of inflammatory cells. However, treatment with graded doses of AESM effectively attenuated these histopathological features, with higher doses demonstrating more pronounced protective effects. In conclusion, these findings suggest that AESM possesses hepatoprotective activity against alcoholic beverage-induced liver damage, and it could be a potential therapeutic agent for mitigating liver injury.